PARADOKS DALAM PENINGKATAN KOMPETENSI GURU PAUD - Hadiqotul Luluk (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
A profesional teacher should have expertice and responsibility supporting by strong professionalem etique. He/She should have competence qualification including intellectual, social, spiritual, character, and moral competence. This article discusses the important role of the teachers for Early Childhood Education in Indonesia. Considering their important tasks and responsibility in educating the children, the article is of the opinion that not anybody or any teacher can become an Early Childhood Education teacher as he/she does not only teach the children but also have to manage and pratise a lot of educational activities and to become the children’s parent at school careing them with love. However, this article observes that the existing efforts to improve the Early Childhood Education teachers’s ]competences have not met the demanded qualification. It is suggested some improvement should be done in the the Early Childhood Education teachers’ education and training.